A retrospective efficacy and safety study of pembrolizumab/cetuximab neoadjuvant therapy in locally advanced hypopharyngeal cancer - Yao, Guangnan; Wu, Xiaobo; Lin, Hanqing; Chen, Zhihong; Lin, Chang; Lin, Gongbiao (Frontiers in Immunology, 2025)
PurposeThe primary objective of this study was to retrospectively assess the efficacy and safety profiles of two neoadjuvant regimens combining either pembrolizumab or cetuximab with paclitaxel and cisplatin in patients with locally advanced hypopharyngeal cancer (LAHPC).MethodsLAHPC patients who received surgical resection at our hospital between August 2022 and February 2024 were enrolled in the study. All patients received neoadjuvant treatment before surgery and postoperative adjuvant therapy. They were categorized into two groups based on the neoadjuvant regimen: the paclitaxel + cisplatin + pembrolizumab (TP + PEMBRO) group and the paclitaxel + cisplatin + cetuximab (TP + CETUX) group. We evaluated various parameters including treatment response rate, adverse effects, surgical modalities, and survival outcomes for both groups.ResultsA total of 32 LAHPC patients were enrolled into the study, with 16 patients in each group. The TP + PEMBRO group demonstrated a significantly superior objective response rate (ORR) of neoadjuvant treatment compared to the TP + CETUX group (87.5% vs 68.75%, P < 0.05). In terms of surgical procedures, the TP + PEMBRO group exhibited a higher proportion of minimally invasive surgeries (87.5% vs 56.25%, P < 0.05), and both the tracheotomy rate and indwelling gastric tube rate were relatively lower in this group. Regarding patient prognosis, the 1-year overall survival (OS) rate in the TP + PEMBRO group was 100%, and the 1-year relapse-free survival (RFS) rate was 92.31%. In contrast, the TP + CETUX group had a 1-year OS rate of 93.75% and a 1-year RFS rate of 81.25%. There was no significant disparity in adverse events between the two groups, and no grade 3–4 severe adverse events occurred.ConclusionThe neoadjuvant TP regimen integrating pembrolizumab or cetuximab was associated with higher transoral surgery (TOS) rates and laryngeal preservation rates. Notably, the TP + PEMBRO regimen outperformed the TP + CETUX regimen in terms of treatment response rate and the proportion of minimally invasive surgeries, suggesting a novel and efficacious neoadjuvant treatment for LAHPC.